Meeting deepwater drilling challenges in Niger-Delta with high performance water-based mud - Chimezie Sidney Uduba; Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Monica Wobo; Antônio Marcos de Oliveira Siqueira; Joshua Kolawole Gbegudu; Franklin Onah Onazi (The Journal of Engineering and Exact Sciences)
High performance water-based mud, a drilling fluid type used for deepwater drilling is posed with similar challenges faced by the aqueous water-based mud used for onshore drilling. These challenges emanate due to high temperature condition encountered in deepwater formations. The challenges include decrease in density, viscosity and other rheological properties of the drilling mud under high temperature condition which can lead to failure to meet drilling objectives. An experimental investigation was carried out on the high-performance water-based mud designed for drilling in the Niger delta region where clay type kaolinite is predominant. Four mud samples were formulated by varying the concentration of Sodium Chloride (NaCl) ranging from 3%, 5%, 7%, and 9% and increasing the temperature from surface condition to 140°F. The properties of the high-performance water-based mud was observed at different salinity concentration. The study shows that the density and viscosity tend to increase with increasing temperature where the mud has high salinity concentration of 7% to 9%. Other rheological properties of the high-performance water-based mud increases at increasing temperature but decreases above 118°F except for the 9% NaCl sample which increases with an increasing temperature. The conclusion drawn from this experimental study is that the increase in NaCl concentration increases the density, viscosity and other rheological properties of the high-performance water-based mud when drilling through deep-water formations under high temperature condition. This has provided solution to the deep-water drilling changes.